Inverse moment problem for non-Abelian Coxeter double Bruhat cells - Gekhtman, M. I. (Methods of Functional Analysis and Topology, 2016)
We solve the inverse problem for non-Abelian Coxeter double Bruhat cells in terms of the matrix Weyl functions. This result can be used to establish complete integrability of the non-Abelian version of nonlinear Coxeter-Toda lattices in GL_n.